2019
DOI: 10.3390/f10040335
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of WRKY Genes and Their Response to Cold Stress in Coffea canephora

Abstract: WRKY transcription factors are known to play roles in diverse stress responses in plants. Low temperatures limit the geographic distribution of Coffea canephora Pierre ex A.Froehner. The WRKYs of C. canephora are still not well characterized, and the response of C. canephora WRKYs (CcWRKYs) under cold stress is still largely unknown. We identified 49 CcWRKYs from the C. canephora genome to gain insight into these mechanisms. These CcWRKYs were divided into three groups that were based on the conserved WRKY dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 54 publications
(140 reference statements)
5
10
0
Order By: Relevance
“…In contrast, sorghum contains fewer WRKY genes than maize, soybean, or rice [ 23 , 45 , 46 ]. The present findings in sorghum, an important cereal crop and a model plant for drought tolerance, add to the recent identification of WRKY genes in a variety of plant species, including chickpea [ 26 ], Chinese jujube ( Ziziphus jujube ) [ 47 ], sugar beet ( Beta vulgaris ) [ 48 ], coffee ( Coffea arabica ) [ 49 ], pepper [ 50 ], eggplant ( Solanum melongena ) [ 51 ], Asian legume crops [ 52 ], sweet potato ( Ipomoea batatas ) [ 53 ], and pearl millet ( Pennisetum glaucum ) [ 54 ].…”
Section: Discussionmentioning
confidence: 66%
“…In contrast, sorghum contains fewer WRKY genes than maize, soybean, or rice [ 23 , 45 , 46 ]. The present findings in sorghum, an important cereal crop and a model plant for drought tolerance, add to the recent identification of WRKY genes in a variety of plant species, including chickpea [ 26 ], Chinese jujube ( Ziziphus jujube ) [ 47 ], sugar beet ( Beta vulgaris ) [ 48 ], coffee ( Coffea arabica ) [ 49 ], pepper [ 50 ], eggplant ( Solanum melongena ) [ 51 ], Asian legume crops [ 52 ], sweet potato ( Ipomoea batatas ) [ 53 ], and pearl millet ( Pennisetum glaucum ) [ 54 ].…”
Section: Discussionmentioning
confidence: 66%
“…TFs are key regulators of gene expression and have a variety of important functions in the plant response to abiotic stress [30,31]. The identification of TFs involved in saline-alkaline stress is crucial to reveal the innate molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In potato, the UDP-glucosyltransferase gene is highly correlated with glucose and gene expression under cold-induced sweetening [ 55 ]. Genome-wide identification of WRKY genes and their response to cold stress in Coffea canephora showed that UDP-glucosyltransferase activity is remarkably represented [ 56 ]. The overexpression of LTG5 increases the CT of rice at the germination stage.…”
Section: Disccussionmentioning
confidence: 99%